Nepričakovani karcinom žolčnika in postopki pri laparoskopski holecistektomiji - Mušič, Mark (Endoskopska revija, 2006)
Background. An estimated one percent of patients operated on for symptomatic gallstones harbour an occult adenocarcinoma. The therapy for incidental carcinoma is based on histopathological staging, which underscores the key role of pathologists in cancer management. Aim. In order to amend the diagnostic and therapeutic standards followed, outcomes of patients treated atthis Department were compared wi.th the results reported by other authors. Patients and Methods. In the past four years (2001-2004), 1,437 patients underwent surgery,for symptoma.tic gallstones at this Department. All gallbladders were sent , for histopathological examination. Carcinoma of tlze gallbladder was diagnosed in seven patients. In one case, incidental carcinomawas found after laparoscopic cholecystectomy, and in four, after coventional surgery. In one of the remaining patients an i.noperable tumor wasdiscovered during laparoscopy. The diagnosis was confirmed by biopsy. Another patient, in whom carcinoma was suspected on the basis of history and ultrasound examination, had a standard operation, which revealed advanced disease with diffuse liver metastases. Results. Postoperative survival ranged from 1 to 15 months. An 85-year-old women was alive at the time of reporting, i.e. at four years after standard cholecystectomy combined with removal of gallstones from the choledochal duct. Postoperative patolzistological examination revealed an occult carcinoma (S1 (pT2) - AJCC/UICC TNM classification). Conclusions. Whenever gallbladder carcinoma is suspected on the basis of history and ultrasound examination, the patient should have a tumor marker assay and additional diagnostic procedures, such as CT and MR imaging. Better survival is expected in patients in whom the diagnosis has been established preoperatively. (Abstract truncated at 2000 characters)
Keywords: Gallbladder Neoplasms; Holecistoktemija laparoskopska; Cholecystectomy, Laparoscopic; Žolčnik, novotvorbe; Zdravljenje, izid; Treatment Outcome; diagnostika; žolčnik; karcinom; laparoskopija; therapy; zdravljenje